Diseño de un sistema de condensación de agua aprovechando la humedad presente en el aire del municipio de Uribia, La Guajira (2021)
In this project, the engineering development of a water condensation system is exposed, taking advantage of the humidity present in the air of the municipality of Uribia, La Guajira, in which the knowledge acquired during the development of the mechanical engineering career is condensed. The climatic and demographic conditions of the municipality in which I proposed the project were determined, later the theoretical bases were determined taking into account the methods by which it is possible to condense the water present in the air, in addition to the equipment with which it is possible to achieve this phenomenon. Based on the above, the functional and operational parameters of the system were established, in order to propose 3 alternatives oriented towards the thermal system. Through the linear weighting method, a vapor compression cycle using a heat exchanger was chosen as the heart of the thermal system, due to the use of a refrigerant for the vapor compression cycle, it was determined that the optimal refrigerant for this a